Fiji : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2002 Article IV Consultation highlights that following the political crisis, Fiji experienced sharp declines in tourism earnings, while external sanctions adversely affected investment and textile exports. As a result, GDP fell 2 3/4 percent in 2000, and the current account deficit widened to 6 1\2 percent of GDP. Financial stability and the basket peg of the Fiji dollar were maintained through tightening of domestic monetary policy and exchange controls, together with government spending cuts to offset the impact of weaker growth on the fiscal deficit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet